Data communications and networking: Practical approach - Bahaman, Nazrulazhar; Hamid , Erman; Mat Ariff, Nor Azman (Venton, 2008)
This book aimed primarily for students who will be taking subject related to this field. All lab activity are divided to four subtopic which is learning outcomes, introduction, hands on exercises with step by step instruction and self review question. This will give the student knowledge about theoretical background of the lab activity and how to implement the activity by follow the procedures.